PORTER'S FIVE FORCES INFLUENCE ON COMPETITIVE ADVANTAGE IN TELECOMMUNICATION INDUSTRY IN KENYA - Mugo, Peter (European Journal of Business and Strategic Management, 2020)
Purpose: Competition is at the core of existence of firms. This determines the appropriateness of a firm's activities that can contribute to its performance, such as innovations, a cohesive culture, or good implementation. Many firms have performed poorly in a competitive environemnt due to failure to analyse and strategise on the Porter's Five Forces, regardless of the industry sector. Competitive strategy aims to establish a profitable and sustainable position against the forces that determine industry competition. The purpose of the study was to investigate the influence of Porter's Five Forces on competitive advantage in telecommunication industry in Kenya. The study aims at establishing the extent to which barriers to entry, rivalry among established firms, bargaining power of buyers, bargaining power of suppliers and substitute products influence competitive advantage of telecommunication industry in Kenya. Methodology:The study adopted desktopresearch. Specifically, the paper identified documentary evidence in the form of already completed studies that focused on influence of porters five forces on competitive advantage both locally, regionally and globally. Findings:The study findings indicated that there was threat of new entrants in the teleommunication industry in kenya due to presence of various competing firms. In addition, although the suppliers in the industry had formed associations to negotiate prices with the input providers, the buyers bargaining power was high. The firms had to strategize on how to attract and retain the customers to avoid shifting from one company to the other. Findings on bargaining power of buyers of mobile phone providers indicate that, firms have spent time and energy in ensuring their customers are well protected and incentivized so as to stick to their respective mobile networks. Similarly, findings on intensity of rivalry, indicate that to strategize and win in this highly competitive industry, product differentiation, process innovation, product innovation and technological innovation are some of the strategies the companies use to stay ahead. Findings on threat of substitute products indicate that, the industry has a number of substitutes that can highly influence the profitability of these companies. The study concludes that porters five forces framework indeed influenced performance of telecommunication firms in Kenya. The study also concludes that the threat of new entrants applies to the mobile phone providers in the Kenyan Telecommunication industry due to the presence of various competing organizations. These organizations are offering similar products and services such as mobile money transfer services, handheld devices, airtime and accessories. Unique contribution to theory, practice and policy The study recommends that the telecommunication firms should keep monitoring their business environment so as to structure the appropriate strategies to keep up with competition and technological changes.